Recovery of dynamic lung function in elite judoists after short-term high intensity exercise - Radovanovic, D.; Bratic, M.; Nurkic, M.; Stankovic, N. (Archives of Budo, 2011)
Background and study aim: Changes to lung volume and capacity occur after intense power output. The aim of this investigation was changes in the parameters of dynamic lung function after short-term high intensity exercise and the correlation between the above mentioned parameters before and after exercise. Material and methods: Changes to the parameters of dynamic lung function (forced vital capacity - FVC, forced expiratory volume during the first second - FEV1.0, and peak expiratory flow - PEF) were studied on a sample consisting of 11 elite judoists (age 21±2.41 years; height 176.63±7.43 cm; weight 75.55±8.91 kg; body fat 8.25±4.38%; VO2max 54.99±4.11 mL.kg-1.min-1). Results: Before and after "all out" Wingate test (peak power 11.95±0.79 W.kg-1; mean power 8.18±0.48 W.kg-1). There are significant difference (p<0.001) among the average values of FVC (1.67±0.63 L or 25.39±9.1 %), FEV1.0 (1.08±0.5 L or 21.1±9.13 %) and PEF (1.85±0.36 L.s-1 or 17.9±3.99 %) which were determined over different periods of time in relation to "all out" test carried out on the subjects. The positive correlation among the FVC, FEV1.0 and PEF determined before the "all-out" test, with the same lung function parameters determined after the test, can indicate that the extent of the manifested power, for elite judoists, has no negative influence on the recovery of dynamic lung function. Conclusion: A lesser reduction in dynamic lung function after short-term high intensity exercise enables a quicker recovery between consecutive attacks, which creates the necessary functional conditions for scoring better results at competitions.